Switching of Single‐Molecule Magnetic Properties of TbIII–Porphyrin Double‐Decker Complexes and Observation of Their Supramolecular Structures on a Carbon Surface. Issue 36 (7th July 2014) - Inose, Tomoko; Tanaka, Daisuke; Tanaka, Hirofumi; Ivasenko, Oleksandr; Nagata, Toshi; Ohta, Yusuke; De Feyter, Steven; Ishikawa, Naoto; Ogawa, Takuji
Abstract Double‐decker complexes based on single‐molecule magnets (SMMs) are a class of highly promising molecules for applications in molecular spintronics, wherein control of both the ligand oxidative states and the 2D supramolecular structure on carbon materials is of great importance. This study focuses on the synthesis and study of 2, 3, 7, 8, 12, 13, 17, 18‐octaethylporphyrin (OEP)–TbIII double‐decker complexes with different electronic structures comprising protonated, anionic, and radical forms. Magnetic susceptibility measurements revealed that only the anionic and radical forms of the OEP–TbIII double‐decker complexes exhibited SMM properties. The barrier heights for magnetic moment reversal were estimated to be 207 and 215 cm−1 for the anionic and radical forms, respectively. Scanning tunneling microscopy (STM) investigations revealed that these OEP–TbIII complexes form well‐ordered monolayers upon simple dropcasting from dilute dichloromethane solutions. All three complexes form an isomorphic pseudo‐hexagonal 2D pattern, regardless of the differences in the electronic structures of their porphyrin–Tb cores. This finding is of interest for SMM technology as ultrathin films of these materials undergoing chemical transformations will not require any detrimental reorganization. Finally, we demonstrate self‐assembly of the protonated 5, 15‐bisdodecylporphyrin (BDP)–TbIII double‐decker complex as an example of successful supramolecular design to achieve controlled alignment of SMM‐active sites.